Sistem Pembayaran Berlangganan WIFI Menggunakan NFC (Near Field Communication) - Nanda Hajiani Putri B (Jurnal Jaringan Telekomunikasi, 2016)
The high use of the internet makes the availability of hotspots a demand for all groups of Indonesian people. The use of computer networks using wifi is widely available in various places, for example in offices, schools, cafes, etc. A person must first login to the wifi network in order to access the internet, the login process is carried out by inputting a username and password, in this process the accuracy of user reading is very necessary, it is not uncommon for users to enter the username and password incorrectly which consists of a fairly long row of numbers and must re-enter it username and password. Therefore, it is necessary to build a support system, namely a wifi subscription payment system using NFC technology on an Android-based smartphone. This NFC technology can help during the login process to a wifi network. Wifi users no longer need to enter a long user name and password to log in, besides that NFC technology is a subscription identity card that can be used anywhere and easy to carry anywhere. This system also makes it easier for wifi corner business owners, because this system performs AAA (Authentication, Authorization, and Accounting) functions for users who want to access an internet network. After making the application, testing is carried out by measuring the reading distance of the NFC reader on the smartphone to the NFC tag.